Effect of Arginine Vasopressin on Intraoperative Hypotension Caused by Oral Administration of 5-Aminolevulinic Acid - Gen Owada; Hideo Nishizawa; Yuki Matoyama; Eri Watanabe; Keigo Mitsuda; Naoki Kaneko; Yasuhiro Kimura; Taikan Nanao; Junichi Fujimoto (Case Reports in Anesthesiology)
5-Aminolevulinic acid (5-ALA) is used for the photodynamic diagnosis of malignant tumors and has been effectively utilized to improve the complete resection rate and reduce the risk of tumor recurrence. However, intraoperative hypotension is a common adverse effect of oral 5-ALA, and it occasionally progresses to severe prolonged hypotension requiring high-dose catecholamine administration. We report a case of intraoperative hypotension due to oral 5-ALA in which arginine vasopressin (AVP) administration was effective for increasing the blood pressure. A 77-year-old man scheduled for a craniotomy for glioma was administered 5-ALA orally before surgery. After the induction of anesthesia, his blood pressure decreased substantially. Although we administered various vasopressor agents, hypotension was prolonged. However, after starting a continuous administration of AVP, the systolic blood pressure increased, and the hemodynamic parameters remained stable during the remainder of the operation. 5-ALA administration may lower blood pressure by inducing nitric oxide production, and AVP inhibits inducible nitric oxide synthase messenger RNA expression and interleukin-1β-stimulated nitric oxide production. In light of these mechanisms, AVP may be a reasonable treatment agent for hypotension induced by 5-ALA.